Formlose Möbel - Hackenschmidt, Sebastian; Noever, Peter; Rübel, Dietmar; Exhibition. Formlose Möbel = Formless furniture. MAK (Österreichisches Museum für angewandte Kunst / Gegenwartskunst) Wien. 2008-05-28. 2008-10-26 (Ostfildern : Hatje Cantz, 2008)
Aagaard Andersen, Gunnar ; AJS Aerolande ; Arad, Ron ; Bär & Knell Design ; Campana Brothers ; Castle, Wendell ; Dean, Roger ; Dixon, Tom ; Gatti, Paolini & Teodoro ; Gehry, Frank O. ; Gruppe Brand ; Gustafsson, Marie-Louise ; Inflate ; Lynn, Greg ; Mauro, Richard ; Mendini, Alessandro ; Myers, Forest ; Nalbach, Gernot & Johanne ; Newson, Marc ; Pesce, Gaetano ; Rashid, Karim ; Remy, Tejo ; Seymour, Jerszy ; Stadler, Robert ; Windels, Lothar ; Zünd-Up / Salz der Erde
boek